Differential regulation of GS-GOGAT gene expression by plant growth regulators in Arabidopsis seedlings - Dragićević, Milan; Simonović, Ana; Bogdanović, Milica; Subotić, Angelina; Ghalawenji, Nabil; Dragićević, Ivana; Todorović, Slađana (Archives of Biological Sciences, 2016)
Primary and secondary ammonium assimilation is catalyzed by the glutamine synthetase-glutamate synthase (GS-GOGAT) pathway in plants. The Arabidopsis genome contains five cytosolic GS1 genes (GLN1;1 – GLN1;5), one nuclear gene for chloroplastic GS2 isoform (GLN2), two Fd-GOGAT genes (GLU1 and GLU2) and a GLT1 gene coding for NADH-GOGAT. Even though the regulation of GS and GOGAT isoforms has been extensively studied in response to various environmental and metabolic cues in many plant species, little is known about the effects of phytohormones on their regulation. The objective of this study was to investigate the impact of representative plant growth regulators, kinetin (KIN), abscisic acid (ABA), gibberellic acid (GA3) and 2,4-dichlorophenoxyacetic acid (2,4-D), on the expression of A. thaliana GS and GOGAT genes. The obtained results indicate that GS and GOGAT genes are differentially regulated by growth regulators in shoots and roots. KIN and 2,4-D repressed GS and GOGAT expression in roots, with little effect on transcript levels in shoots. KIN affected all tested genes; 2,4-D was apparently more selective and less potent. ABA induced the expression of GLN1;1 and GLU2 in whole seedlings, while GA3 enhanced the expression of all tested genes in shoots, except GLU2. The observed expression patterns are discussed in relation to physiological roles of investigated plant growth regulators and N-assimilating enzymes.